Calcium Positively Mediates Blue Light-Induced Anthocyanin Accumulation in Hypocotyl of Soybean Sprouts - Hu, Gang; Yue, Xiaomeng; Song, Jinxue; Xing, Guipei; Chen, Jun; Wang, Haixia; Su, Nana; Cui, Jin (Frontiers in Plant Science, 2021)
Soybean sprouts are flavorful microgreen that can be eaten all year round, widely favored in Southeast Asia. In this study, the regulatorymechanism of calcium on anthocyanins biosynthesis in soybean sprouts under blue light was investigated. The results showed that blue light, with short wavelength, effectively induced anthocyanins accumulation in hypocotyl of soybean sprouts cultivar ‘Dongnong 690’. Calcium supplementation further enhanced anthocyanins content, which was obviously inhibited by LaCl3 and neomycin treatment. Moreover, exogenous calcium changed the metabolism of anthocyanins, and seven anthocyanin compounds were detected. The trend of calcium fluorescence intensity in hypocotyl cells, as well as inositol that of the 1,4,5-trisphosphate and calmodulin content, were consistent with that of anthocyanins content. Specific spatial distribution patterns of calcium antimonate precipitation were observed in the ultrastructure of hypocotyl cells under different conditions. Furthermore, calcium application upregulated the expression of genes related to anthocyanins biosynthesis, while calcium inhibitors suppressed these genes . Finally, transcriptomics was performed to gain global insights into the molecular regulation mechanism of calcium-associated anthocyanin production. Genes from the flavonoid biosynthesis pathway were distinctly enriched among the differentially expressed genes, and the weighted gene co-expression network analysis showed that two MYBs were related to the accumulation of anthocyanins. These results indicated that calcium released from apoplast and intracellular stores in a specific spatial-temporal features promote blue light-induced anthocyanins accumulation by upregulating the expression of genes related to anthocyanins synthesis in ‘Dongnong 690’ hypocotyl. Our findings deepen our understanding of calcium regulation mechanism of blue light-induced anthocyanins accumulation in soybean sprouts, which will help growers produce high-quality foods beneficial for human health.